2023
DOI: 10.1109/access.2023.3273898
|View full text |Cite
|
Sign up to set email alerts
|

Twitter Sentiment Analysis-Based Adjustment of Cryptocurrency Action Recommendation Model for Profit Maximization

Abstract: Cryptocurrencies have recently attracted considerable attention, resulting in research mainly on deep learning-based price prediction models to maximize profit. Two research approaches have been adopted. Studies adopting the first approach directly predict the future cryptocurrency price. Long short-term memory (LSTM) and gated recurrent unit (GRU), which show high performance in time-series data, are mainly used for this approach. Further, studies adopting the second approach recommend actions to investors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The sentiment surrounding Bitcoin holds considerable influence in accurately forecasting Bitcoin prices, even when accounting for other pertinent elements. Moreover, empirical data suggests that the attitude surrounding the prevailing cryptocurrency, specifically Bitcoin, exerts an influence on the value of other cryptocurrencies (Anamika et al ., 2023; Park and Seo, 2023; Kyriazis et al ., 2023).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The sentiment surrounding Bitcoin holds considerable influence in accurately forecasting Bitcoin prices, even when accounting for other pertinent elements. Moreover, empirical data suggests that the attitude surrounding the prevailing cryptocurrency, specifically Bitcoin, exerts an influence on the value of other cryptocurrencies (Anamika et al ., 2023; Park and Seo, 2023; Kyriazis et al ., 2023).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The movie recommendation system efficiently assists users in discovering movies that match their preferences, whether derived from their own experiences or from the other users. Hence, sentiment analysis is implemented to reviews/comments to also contribute to movie ratings and lead to better recommendations [13]. Multi-domain sentiment analysis approaches focus on developing models to transfer information between different domains.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of Park et al, to predict the closing prices of cryptocurrencies, the performance evaluation of a genetic algorithm tuned for deep learning (DL) and boosted treebased techniques was investigated [25]. By comparing the results of Convolutional Neural Networks (CNN), Deep Forward Neural Networks, and Gated Recurrent Units, it was found that the CNN model had the least mean average percentage error of 0.08 and produced a consistent and highest explained variance score of 0.96 (on average) compared to other models [26]. In another study, long shortterm memory (LSTM) and gated recurrent unit (GRU) were used to predict the future prices of cryptocurrencies, and according to the Twitter sentiment analysis, an action recommendation model was proposed to recommend actions to investors for maximizing profits, such as "sell", "buy " , and "wait".…”
Section: Introductionmentioning
confidence: 99%